2013
DOI: 10.1007/s11095-013-1067-7
|View full text |Cite
|
Sign up to set email alerts
|

The Immunogenicity of Polyethylene Glycol: Facts and Fiction

Abstract: An increasing number of pegylated therapeutic proteins and drug targeting compounds are being introduced in the clinic. Pegylation is intended to increase circulation time and to reduce an immunogenic response. Recently however a number of publications have appeared claiming that the polyethylene glycol (PEG) moiety of these products in itself may be immunogenic and that the induced anti-PEG antibodies are linked to enhanced blood clearance and reduced efficacy of the products. A critical review of the literat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
206
0
5

Year Published

2013
2013
2016
2016

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 311 publications
(213 citation statements)
references
References 26 publications
2
206
0
5
Order By: Relevance
“…Polyethylene glycol (PEG) polymers have become widely used to improve the pharmacokinetics of therapeutic peptides by improving half-life and reducing the susceptibility to proteolytic degradation resulting in many commercial therapeutic peptide products (60)(61)(62). However, there are concerns about the toxicological effects (i.e., renal toxicity), the metabolic fate of the PEG moiety and immunogenicity (63,64). The latter having the opposite intended effect in that induced anti-PEG antibodies have been linked to enhanced blood clearance and reduced efficacy of the therapeutic.…”
Section: Proteolytic Degradation and Hydrolysismentioning
confidence: 99%
“…Polyethylene glycol (PEG) polymers have become widely used to improve the pharmacokinetics of therapeutic peptides by improving half-life and reducing the susceptibility to proteolytic degradation resulting in many commercial therapeutic peptide products (60)(61)(62). However, there are concerns about the toxicological effects (i.e., renal toxicity), the metabolic fate of the PEG moiety and immunogenicity (63,64). The latter having the opposite intended effect in that induced anti-PEG antibodies have been linked to enhanced blood clearance and reduced efficacy of the therapeutic.…”
Section: Proteolytic Degradation and Hydrolysismentioning
confidence: 99%
“…PEG polymers have been extensively used to improve the pharmacokinetics of biologics. (21) Despite recent concerns about potential immunogenicity of PEG, (22) this remains controversial, (23) and they are still the polymer of choice for in vivo applications.…”
Section: Introductionmentioning
confidence: 99%
“…This recommendation has proven to be a tall order, as developing and validating assays to detect antibodies against a PEG moiety is a major challenge. In a review paper by Schellekens et al (3), the authors concluded that most, if not all, assays used for detecting anti-PEG antibodies are flawed due to the lack of specificity as well as poor characterization of positive controls (3,4). Until recently, traditional bridge immunoassay format assays have been able to detect anti-PEG IgM antibodies but have struggled to detect IgG isotype antibodies with sufficient sensitivity in human matrix (5,6), suggesting that the type of PEG and/or protein therapeutic may play a role.…”
Section: Introductionmentioning
confidence: 99%